Pengaruh Right Issue dan Kurs Rupiah Terhadap Harga Saham Syariah Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Suci Wulandary, Anissa; Sarifudin, Ahmad (TSARWAH, 2023)
This study explores the impact of Right Issue and the exchange rate (kurs Rupiah) on the stock prices of Sharia-compliant companies listed on the Indonesia Stock Exchange from January 2017 to May 2022. Utilizing purposive sampling, 41 companies were selected for analysis using the multiple linear regression model and Eviews 10 software. The results reveal that Right Issue significantly negatively affects Sharia stock prices (t-value < t-table, -2.217714 < 2.02809, p = 0.0336 < 0.05). Conversely, the exchange rate (kurs Rupiah) does not significantly impact Sharia stock prices (t-value < t-table, -1.140584 < 2.02809, p = 0.2623 > 0.05). Simultaneously, both variables significantly influence Sharia Stock Prices (F-value = 4.13, p = 0.044863 < 0.05), indicating their combined positive and negative effects. Right Issue and Kurs Rupiah can be used as indicators of a company's value or stock price. The R-squared value is 0.171493 or 17%, implying that 17% of the variability in Sharia Stock Prices is explained by these variables. In conclusion, Right Issue and Kurs Rupiah contribute to a 17% influence on Sharia Stock Prices, while the remaining 83% is influenced by unexplored variables.